2017
DOI: 10.18203/2320-1770.ijrcog20170007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of vaginal delivery and caesarean section in antepartum eclampsia at tertiary care hospital

Abstract: Background: Eclampsia is characterized by the sudden onset of generalized tonic clonic seizures. Eclampsia is usually preceded by a history of the pre-eclampsia but rarely arises in a woman with minimally increased blood pressure and no proteinuria. Eclampsia most commonly occurs in the third trimester, though rarely eclampsia may occur before 20 wks in molar or multiple pregnancy. The aim of the study was to compare maternal and fetal outcome in antepartum eclampsia when terminated by vaginal delivery and cae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
2
4
1
Order By: Relevance
“…In this study, the caesarean delivery rate was slightly higher than that of women who had normal vaginal delivery. This contrasts with the findings from the study done by Priti Kumari and colleagues, in which the rate of vaginal delivery was higher than that of caesarean delivery [ 9 ]. However, in most studies across the world, caesarean section delivery has been repeatedly reported to be higher in women with eclampsia [ 10 12 ].…”
Section: Discussioncontrasting
confidence: 90%
“…In this study, the caesarean delivery rate was slightly higher than that of women who had normal vaginal delivery. This contrasts with the findings from the study done by Priti Kumari and colleagues, in which the rate of vaginal delivery was higher than that of caesarean delivery [ 9 ]. However, in most studies across the world, caesarean section delivery has been repeatedly reported to be higher in women with eclampsia [ 10 12 ].…”
Section: Discussioncontrasting
confidence: 90%
“…The incidence rate correlates with 10.20% for Leduc et al (1992). [9] The incidence of maternal mortality in our study was 4%, which well co-relates with that conducted by Hagragi (2006) [10] was found to be 2.3%. The incidence of perinatal mortality in our study was 18%, which is comparable to Gaddi et al (2001) [11] 22.3%.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the caesarean delivery rate was slightly higher than that of women who had normal vaginal delivery. This contrasts with the ndings from the study done by Priti Kumari and colleagues, in which the rate of vaginal delivery was higher than that of caesarean delivery [7]. However, in most studies across the world, caesarean section delivery has been repeatedly reported to be higher in women with eclampsia [8 10].…”
Section: Discussionmentioning
confidence: 82%